Our Everyday Science: Spreading science through experiments - de Paula, Everton Luiz; Armini Ruela, Fernando; de Souza Santos, Crislane; Kato, Kelly Cristina; Costa, Camila Marques; de Souza, Franck Henrique (Guará Journal, 2019)
This paper presents the results of an extension project with experi-mentation, carried out in the city of Diamantina, Minas Gerais, in the years 2016-2017. The project was operationalized through practical experiments with the objective of encouraging students’ interest and complementing with experimental activities the disciplines of Phys-ics, Chemistry and Biology in the process of teaching-learning. The target audience was high school students (1st to 3rd year) and 662 (six hundred and sixty-two) students from the State Schools Ayna Torres and Gabriel Mandacaru, located in the city of Diamantina, and the State School Joviano de Aguiar, located in the city of Gouveia, both in “Vale do Jequitinhonha”, a macroregion of Minas Gerais. The results show the importance of the experimental activities for the teaching and learning of sciences that have aroused students’ attention, stim-ulating them to adopt critical attitudes towards problems, able to develop the capacity to understand some phenomena present in their daily life and encouraging to use this instrument for the con-struction and transmission of knowledges, in addition to enabling the university-community approach.